The cognitive meaning of the concept of “death” in Shakarim’s poems - Amanbekkyzy, Zh.; Syzdykova, G.O.; Husainova, L.M. (Karagandy University of the name of academician E.A. Buketov, 2025)
This article examines the cognitive meaning of the concept of “death” in the poetry of Shakarim Kudaiberdiuly. The study aims to explore the linguistic features that shape the understanding of “death” in Shakarim’s works. Within the framework of linguoculturology, the research seeks to establish the relationship between language and culture by analyzing the concept’s structure, semantic and informational fields, cognitive essence, and research methodology. The study draws upon Shakarim Kudaiberdiuly’s poetry, as well as phraseological, explanatory, ethnolinguistic, and ethnographic dictionaries as primary sources. The scientific and methodological basis of the study is grounded in findings from cognitive linguistics and psycholinguistics. The novelty of this research lies in providing a comprehensive description of the concept of “death” through cognitive and linguocultural analysis. The theoretical value of the results is revealed in demonstrating the relevance of the worldview in Shakarim’s poems through the concept of “death”, and the materials will serve as a foundation for future research in cognitive linguistics and linguoculturology. The article explores the conceptual field of “death” as presented in dictionary definitions, following the methodology of conceptual analysis by V.A. Maslova. It examines the concept’s reflection in phraseological units and proverbs, highlighting its linguistic and cultural significance in Shakarim Kudaiberdiuly’s poetry. The study employs textual analysis and comparative-historical methods to systematically analyze proverbs and sayings about life within the poems, revealing their semantic features and cognitive significance. The findings contribute to a deeper understanding of the spiritual values of the Kazakh people and offer insights for their adaptation in contemporary contexts.
Шәкәрім өлеңдеріндегі «өлім» концептісінің танымдық мәні
Познавательный характер концепта «смерть» в стихах Шакарима
Keywords: concept; metaphor; emotion; proverb; phraseology